ANALYSIS OF THE MATHEMATICAL COMMUNICATION ABILITY OF CLASS VII STUDENTS OF SMP NEGERI 1 ULUNOYO ON ASSOCIATION MATERIALS IN SAMBULU VILLAGE - Leni Marlina Laia; Defi Susanti Duha; Defi Yanti Hulu (Universitas Nias Raya, 2023)
This research is motivated by the importance of having mathematical communication skills in the set material. Mathematical communication skills are abilities that need to be developed in learning mathematics. The purpose of this study was to determine students' mathematical communication skills in learning mathematics for class VII SMP Negeri 1 Ulunoyo in Sambulu Village; This type of research is a qualitative research with a descriptive approach with the research population of all seventh grade students of SMP Negeri 1 Ulunoyo in Sambulu Village. The data were analyzed by the steps of data collection, data presentation and drawing conclusions. The research instrument used was a test of mathematical communication skills and an unstructured interview guide. The results showed that the mathematical communication skills of seventh grade junior high school students in Sambulu Village were still low where: 1) students were still unable to make mathematical models; 2) students have difficulty in interpreting the solution so that the problem solving process is wrong or incorrect; 3) students have difficulty in solving story problems. Through this research, the researcher suggests that students' mathematical communication skills should be further improved by practicing math problems related to mathematical communication.